Evaluation of a Social Media Campaign on Youth Mental Health Stigma and Help-Seeking. Issue 1 (11th November 2020) - Thompson, Aaron; Hollis, Steve; Herman, Keith C.; Reinke, Wendy M.; Hawley, Kristin; Magee, Shawndrea
ABSTRACT: Mental health (MH) stigma affects help seeking behaviors of youth, particularly youth of color. This article reports the impact of Look Around (LA), a social media campaign designed to reduce MH stigma and increase help seeking in 6th- to 12th-grade youth in one Midwestern county. The campaign utilized movie theater advertising, social media, web-based advertising, and school-based media/events over a school year. Using a pre–posttest survey research design with 11, 478 6th- to 12th-grade students in a Midwestern county, we used paired t -tests to examine pre- to posttest changes in survey items addressing MH stigma and help seeking attitudes. We then used a regression model to examine change by racial subgroup on a composite of all the items. Lastly, we used an independent t -test to examine differences between high-change youth and low-change youth on academic performance, attendance, discipline, and MH screening scores. Posttest improvements in the stigma and help-seeking for all youth were observed, but controlling for all covariates (grade level, sex, etc.), youth of color reported lower levels of change compared to White youth. Social media campaigns are useful in addressing MH stigma and help seeking, but messaging may need to attend to the cultural characteristics of all youth.